Penerapan Model Contextual Teaching Learning Berbantuan Komika (Komik Matematika) untuk Siswa Sekolah Dasar - Tika Aprilia (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2021)
This study aimed to describe the improvement of mathematics learning outcomes in grade V at SDN Gajahmungkur 02 Semarang. This research was a classroom action research conducted in 3 cycles, each cycle consists of two meetings. The results showed that: (1) teacher skills in the first cycle score was 35,5 (good); in the second cycle score was 43,5 (very good); and in the third cycle score was 47 (very good), (2) students’ activity in the first cycle score was 28,2 (good); in the second cycle score was 31,2 (very good); and in the third cycle score was 34,8 (very good), (3) learning ambiance in first cycle obtained 5,5 (good); in the second cycle got  6,5 (very good); and in the third cycle reached 7,5 (very good), (4) learning material in first cycle obtained 6 (very good); in the second cycle got 6,5 (very good); and in the third cycle reached 8 (very good), (5) learning media in first cycle obtained 8 (good); in the second cycle got 10 (very good); and in the third cycle reached 12 (very good), (6) learning result of students’ learning outcome in first cycle obtained 69,2%; in the second cycle got 76,9%; and in the third cycle reached 88,5%. Thus, the application of the contextual teaching learning model assisted by mathematics comic media can improve student learning outcomes.  Keywords: Contextual Teaching Learning, Mathematical Comics, Student Learning Outcomes, Elementary School========================================================================================================Tujuan penelitian ini adalah mendeskripsikan peningkatan hasil belajar matematika pada siswa kelas V SDN Gajahmungkur 02 Semarang. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan 3 siklus, setiap siklus terdiri dari 2 pertemuan. Hasil penelitian menunjukkan: (1) keterampilan guru siklus I skornya 35,5 (baik), siklus II skornya 43,5 (sangat baik), siklus III skornya 47 (sangat baik), (2) aktivitas siswa siklus I skornya 28,2 (baik), siklus II skornya 31,2 (baik), siklus III skornya 34,8 (sangat baik), (3) iklim pembelajaran siklus I skornya 5,5 (baik), siklus II 6,5 (sangat baik), siklus III 7,5 (sangat baik), (4) materi pembelajaran siklus I skornya 6 (sangat baik), siklus II 6,5 (sangat baik), siklus III 8 (sangat baik), (5) media pembelajaran siklus I skornya 8 (baik), siklus II 10 (sangat baik), siklus III 12 (sangat baik), (6) hasil belajar siklus I memperoleh ketuntasan belajar 69,2%, siklus II 76,9%, siklus III 88,5%. Dengan demikian penerapan model contextual teaching learning berbantuan media komik matematika dapat meningkatkan hasil belajar siswa. Kata kunci: Contextual Teaching Learning, Komik Matematika, Hasil Belajar Siswa, Sekolah Dasar